Functional differences stabilize beetle communities by weakening interspecific temporal synchrony - van Klink, Roel; Lepš, Jan; Vermeulen, Rikjan; de Bello, Francesco (Ecology, 2019)
The temporal stability of communities is essential for the maintenance of ecosystem functioning across trophic levels. The stabilizing effect of biodiversity is, among other factors, modulated by the level of synchrony in population fluctuations among the species in the community. What drives community synchrony, however, remains largely unclear. Community synchrony can be affected by external drivers such as disturbances, but also by the properties of the community. Species with different ecological strategies should fluctuate less synchronously than more similar species; thus, an increase in diversity of ecological strategies should decrease synchrony, and increase the stability of the community. Here, using an exceptionally large data set of ground beetle trappings in Dutch heathlands (~370,000 individuals in 19 plots, each sampled between 9 and 36 yr), we assess the drivers of community stability and synchrony, and their relationship with disturbance, species richness, and functional diversity (FD). We found no effect of disturbance (fire and topsoil removal) on community stability or synchrony, probably because of unpredictable patterns of increase or decrease of the populations. Community synchrony was overall positive, giving more support for independent and positive correlation between species than for compensatory dynamics. Synchrony decreased with increasing FD, but not with species richness. Supporting this, we found that the more species pairs differ in their traits, the less synchronously their populations fluctuate, where 74% of all pairs showed no significant correlation. Significant positive synchrony (19% of species pairs) was concentrated among pairs with low trait dissimilarity, and the 7% of pairs with significant negative temporal correlation showed no relation with pairwise functional dissimilarity. The stabilizing effect of FD via decreased synchrony supports largely untested theoretical expectations that an increased diversity of functional strategies in a community will have a stabilizing effect on community abundance. We hypothesize that because competition is low in this community, the stabilizing effect of FD reflects interspecific variation in responses to environmental fluctuations rather than competition.
Keywords: Biodiversity; Coleoptera; brouci; ekosystém; biodiverzita; Animals; Ecology; ekologie; Ecosystem; zvířata